Identification technology for city freeway users based on XDR big data analysis - Baoyou WANG; Saibin YAO; Jiucheng HUANG; Hui PAN (Dianxin kexue)
In the scene of city freeway, the driving speed is relatively faster, the flow of people is denser, and the customers have higher requirements for communication experience.Firstly, the architecture of big data platform for mobile network quality control was introduced.Then, the identification algorithm for city freeway users based on XDR big data analysis was proposed.Finally, through XDR big data analyzing and processing, the user track on freeway was output, which followed by matching with the fingerprints database of freeways.The identification accuracy for city freeway users was improved, and wireless network quality monitoring of city freeways was supported.